Hypoglycemic and Antidiabetic Effect of Pleurotus sajor-caju Aqueous Extract in Normal and Streptozotocin-Induced Diabetic Rats - Sze, Han Ng; Mohd Zain, Mohd Syazwan; Wan Rosli, W. I. (Hindawi, 2015)
Introduction. Pleurotus sajor-caju (PSC) is an edible oyster mushroom featuring high nutritional values and pharmacological properties. Objective. To investigate the hypoglycemic and antidiabetic effects of single and repeated oral administration of PSC aqueous extract in normal and diabetic rats. Materials and Methods. A single dose of 500, 750, or 1000mg/kg of the PSC extract was given to experimental rats to determine the effects on blood glucose (BG) and oral glucose tolerance test (OGTT). The effective dose (750mg/kg) of PSC extract was repeatedly administrated daily for 21 days in diabetic rats to examine its antidiabetic effects in terms of BG control, body weight, urine sugar, HbA1c, and several serum profiles. Results.The dose of 750 mg/kg showed the most significant BG reduction (23.5%) in normal rats 6 hours after administration in BG study (